Measurement of the Physiological Workload of Sorting Station Operators in A Palm Oil Processing Factory - Sitorus, Tosty Maylangi; Lubis, Rizki Fadhillah; Tamami, Briliyan (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
One of the palm oil processing industries in Riau that has isolated entrepreneurs as part of its work. Based on the results of continuous observations using the Nordic Body Map (NBM) Questionnaire, 75% of working waste handlers experience complaints in the hands, waist, and legs. So the workload of processing operators is measured using a physiological approach in one of the palm oil processing industries in Riau. Measurements using a physiological approach are carried out objectively using the method of heart rate, energy expenditure, %CVL, and energy consumption. Based on the principles of heart rate, energy expenditure budget and %CVL, the results were found to be non-standard which requires additional improvements based on the energy expenditure budget and %CVL method.